2020
DOI: 10.1016/j.cimid.2020.101494
|View full text |Cite
|
Sign up to set email alerts
|

Microbial diversity involved in the etiology of a bovine respiratory disease outbreak in a dairy calf rearing unit

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 58 publications
(105 reference statements)
2
21
0
Order By: Relevance
“…In Brazil, information relative to the occurrence of BRD is limited when compared with studies from North America (25)(26)(27)(28) and Australia (29,30). Previous studies done in Brazil were designed to investigate a single (31)(32)(33)(34)(35)(36)(37) or several agents (2,16,(38)(39)(40)(41)(42)(43) associated with BRD. These studies focused on the molecular identification of agents, with and without the histopathologic diagnosis of the patterns of pulmonary disease.…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, information relative to the occurrence of BRD is limited when compared with studies from North America (25)(26)(27)(28) and Australia (29,30). Previous studies done in Brazil were designed to investigate a single (31)(32)(33)(34)(35)(36)(37) or several agents (2,16,(38)(39)(40)(41)(42)(43) associated with BRD. These studies focused on the molecular identification of agents, with and without the histopathologic diagnosis of the patterns of pulmonary disease.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the 5' UTR region of BVDV revealed that the BVDV wild-type strains (UEL15-BR/18 and UEL16-BR/18) were 100% identical to each other, and that the nt identity ranged from 97-97.8% with the 16/111 and F BVDV-1d prototype strains (Vilcek et al 2001). The analysis also revealed 99.1-99.5% nt identity with other Brazilian BVDV-1d strains, namely, UEL2-BR/07 (Otonel, et al 2014), UEL6-BR/11, UEL7-BR/11 (Headley et al 2014), and UEL11-BR/11 (Oliveira et al 2020). Based on the nt sequences obtained from the N pro gene, the BVDV wild-type strains exhibited 99.5% nt identity to each other, and 90.2% identity with the F BVDV-1d prototype strain (Vilcek et al 2001).…”
Section: Resultsmentioning
confidence: 84%
“…Diverging from the trend of global literature (Martin, Bateman, Shewen, Rosendal, & Bohac, 1989;Fulton, Cook, Step, Confer, & Saliki, 2002;Murray, More, Sammin, Casey, & McElroy, 2017), there are few reports of BPIV-3 associated with the development of BRD in Brazil. This infectious disease agent was not identified in several studies (Brasil et al, 2013;Baptista et al, 2017;Headley, Okano, Balbo, Marcasso, & Oliveira, 2017;Oliveira & Dall Agnol, et al, 2020), but was associated with few cases of mixed infections in cattle from Brazil (Oliveira & Pelaquim, et al, 2020). A retrospective study done by our group identified singular BPIV-3 infections in only 6.6% (1/15 of all diagnoses) of interstitial pneumonia (Oliveira & Pelaquim, et al,2020).…”
Section: Bacterialmentioning
confidence: 99%
“…Several studies done in Brazil have demonstrated concomitant action of respiratory agents of BRD (Baptista et al, 2017;Beuttemmuller et al, 2017;Magalhães et al, 2017;Tortorelli et al, 2017;Gaeta, Ribeiro, Alemán, Yoshihara, & Nassar, 2018;Oliveira & Pelaquim, et al 2020;Oliveira & Dall Agnol, et al 2020) using molecular identification with or without histopathological and immunohistochemical diagnoses. This trend of concomitant infections in BRD is evident in other countries such as in the USA (Fulton et al, 2009;Schneider, Tait, Busby, & Reecy, 2009;Taylor et al, 2010), Canada (Gagea et al, 2006;Booker, Abutarbush, Morley, Jim, & Pittman, 2008;Jim, 2009), and Australia (Cusack, McMeniman, & Lean, 2003;Moore et al, 2015;Hay et al, 2016).…”
Section: Bacterialmentioning
confidence: 99%